Parallel Multiphysics Simulations of Charged Particles in Microfluidic Flows - Bartuschat, Dominik; Rüde, Ulrich (Journal of Computational Science, 2015)
<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; line-height: 23.68px; word-spacing: -1.24453px;">The article describes parallel multiphysics simulations of charged particles in microfluidic flows with the waLBerla framework. To this end, three physical effects are coupled: rigid body dynamics, fluid flow modelled by a lattice Boltzmann algorithm, and electric potentials represented by a finite volume discretisation. For solving the finite volume discretisation for the electrostatic forces, a cell-centred multigrid algorithm is developed that conforms to the lattice Boltzmann meshes and the parallel communication structure of waLBerla. The new functionality is validated with suitable benchmark scenarios. Additionally, the parallel scaling and the numerical efficiency of the algorithms are analysed on an advanced supercomputer.
Keywords: Parallel simulation; Electrokinetic flow; Fluid–particle interaction; Cell-centered multigrid; MPI